Biological Assets Accounting for Patchouli MSMEs: Enhancing Financing and Exports - Putri Nugrahaningsih; Zaim Arif Eko Saputro; Galuh Tiaramurti; Labbaika Dwi Ayu Rahmawati; Denty Arista; Emy Dwi Nursulistyo; Bayu Seto (Jurusan Akuntansi Politeknik Negeri Malang, 2026)
Purpose: this article observes the transformation of Patchouli MSMEs accounting through introduction of PSAK 241 and its contribution towards access to finance and export capacity upgrading.Method: qualitative case study using in-depth interviews, direct observation, and documentation as sources of data.Results: implementing PSAK 241 will enhance the quality of financial reporting because it can appropriately present Biologic Assets and increasing the trust from financing Institutions as well as business partners.Novelty: deep analyze at PSAK 241 implementation in small business farm with biological assets like patchouli.Contribution: provide practical guidance to help MSMEs comply with accounting regulations. Abstrak: Akuntansi Aset Biologis untuk UMKM Patchouli: Peningkatan Pembiayaan dan EksporTujuan: untuk mengamati transformasi akuntansi UMKM Patchouli melalui pengenalan PSAK 241 dan kontribusinya terhadap akses ke pembiayaan serta peningkatan kapasitas ekspor.Metode: studi kasus kualitatif menggunakan wawancara mendalam, pengamatan langsung, dan dokumentasi sebagai sumber data. Hasil: dengan menerapkan PSAK 241, pelaporan keuangan akan menjadi lebih berkualitas karena dapat secara tepat menyajikan Aset Biologis, yang meningkatkan kepercayaan dari lembaga pembiayaan serta mitra bisnisKebaruan: melakukan analisis mendalam terhadap PSAK 241 pada usaha kecil di sektor pertanian yang memiliki aset biologis seperti patchouli.Kontribusi: memberikan panduan praktis untuk membantu UMKM mematuhi peraturan akuntansi.